THE CONCEPT OF DIGITAL ASSETS AND THEIR LEGAL ASPECTS - Jololiddinova Dilara Zovki kizi (American Journals, 2025)
This article examines the concept of digital assets, focusing on their definitions, classifications, and the evolving role they play in the modern digital economy. It analyzes the key legal aspects of digital assets, including ownership rights, transferability, protection mechanisms, and the challenges arising from their regulation. The study reviews current legislation and judicial practices related to digital assets, identifying existing gaps and inconsistencies in legal frameworks across different jurisdictions. The purpose of this research is to provide a comprehensive understanding of how digital assets are integrated into contemporary legal systems and to discuss potential directions for developing effective legal regulation that ensures stability, security, and legal certainty in the digital sphere.
Keywords: Digital assets, legal aspects, ownership, regulation, blockchain, cryptocurrencies, intellectual property, digital economy, legal frameworks, asset protection